THE ROLE OF SUSTAINABILITY REPORTING IN INCREASING THE VALUE OF BANKING COMPANIES IN 2021-2024 - Stefanus Putra Pradana; Yuana Rizky Octaviani Mandagie (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2026)
This study aims to analyze the effect of sustainability reporting based on Environmental, Social, and Governance (ESG) on the firm value of banking companies in Indonesia during the 2021–2024 period. The research sample consists of 25 banking companies that consistently publish sustainability reports. ESG disclosure is measured based on the GRI Standards 2021, while firm value is proxied by Price to Book Value (PBV). The analytical method used is panel data regression with model testing conducted through the Chow test, Hausman test, and Lagrange Multiplier test. The results show that ESG-based sustainability reporting contributes to an increase in firm value, indicating that transparency and commitment to sustainability are important factors in creating long-term value and strengthening investor confidence in the banking sector.